Initial stages of Pt(111) electrooxidation: dynamic and structural studies by surface X-ray diffraction. (10th January 2017) - Drnec, Jakub; Ruge, Martin; Reikowski, Finn; Rahn, Björn; Carlà, Francesco; Felici, Roberto; Stettner, Jochim; Magnussen, Olaf M.; Harrington, David A.
Abstract: In-situ surface X-ray diffraction is used to characterize the surface oxides on a Pt(111) surface in 0.1 M HClO4 . Detailed analysis at two potentials confirms that the surface restructuring in the initial oxidation stages is consistent with a place exchange process between Pt and O atoms, and the exchanged Pt atoms are located above their original positions in the Pt(111) lattice. The (1, 1, 1.5) reflection is used to dynamically study the surface during cyclic voltammetry. The restructuring associated with the place exchange initiates with the CV peak at 1.05 V, even though multiple cycles to 1.17 V lead to no changes in the CV. The restructuring is reversible below a critical coverage of place exchanged Pt atoms, which we estimate to be between 0.07 and 0.15 ML. Extensive cycling to potentials higher or equal to 1.17 V leads to progressive disordering of the surface.